The familial experiences of Malay adolescents with conduct issues: an interpretative phenomenological analysis IPA - Daud, Mohd Najmi; Coombes, Leigh; Venkateswar, Sita; Ross, Kirsty; Madon, Zainal (Turkish Online Jounal of Qualitative Inquiry, 2021)
This research explores how Malay adolescents with behavioural issues make sense of their family life experiences. This research utilised Interpretative Phenomenological Analysis (IPA). This research involved eight (8) Malay male participants, aged between 16 and 18 years. The participants who were selected through purposive sampling were recruited from a rehabilitation centre for young offenders in Malaysia. The participants attended at least two semi-structured interview sessions. Each interview session was conducted in Malay, and each session lasted between 50 and 60 minutes. These interviews, which were digitally audiotaped, were then transcribed, checked and verified accordingly, translated from Malay into English, and analysed using the IPA method. The results suggest that the participants understanding of their family lived experiences is constructed reflective to the complex relationship between the traditional Malay cultures, values, beliefs and practices, which are much influenced by Islamic teaching, the emergent new values and worldviews associated with globalisation and modernisation. Through the emerging themes, the participants pictured that the interactions between family members, parents were essential to them. But their interpretation of such interactions had conflicting values with the normality of the local belief and practices, which played roles in their criminal engagement. Thus, it can be understood that these affected adolescents were not necessarily problematic internally, but they just reacted to the changing context around them, especially to their family institution.